Effects of matrix composition and Eu³⁺ concentration on luminescence properties of phosphate glass - Polisadova, E.F.; Othman, H.A.; Lisitsyn, V.M. (Functional Materials, 2013)
The effect of Li₂O and ZnO content and Eu³⁺ ion concentration in the glass composition on the decay of luminescence was investigated in phosphate glasses of composition P₂O₅—Li₂O—ZnO . The emission was excited by high-current electron beam of nanosecond duration with an electron energy of 200 eV. It was found that in the range of 0.5—3 wt.% Eu₂O₃ the decay time depends weakly on europium ion concentration. The increase of ZnO (with parallel reduction of Li₂O ) leads to a shortening the decay time of luminescence in the bands at 592 and 614 nm of 2.1 to 1.5 ms. This is due to the symmetry reduction of the Eu³⁺ ion environment. The rise of luminescence signal with duration of some microseconds in the kinetics of the luminescence peak at 614 nm was observed.